Assessment of Different Detection Methods in Bacteria Survival on Cotton and Polyester Textiles - Katarzyna Jekiel; Justyna Syguła-Cholewińska (Journal of Natural Fibers)
Textiles are an important material used as personal protective equipment (PPE) not only in the hospital environment but also in the industrial area during the production of food or cosmetics. Fabrics have a close contact with human skin and therefore they are the great source of pathogens and cause cross-contamination. The best objective of this study was to determine the survivability of three common bacteria on four different textiles. The significant difference in recovery of bacteria from textiles was recorded after 1, 7, and 14 days. In the culture method Pseudomonas aeruginosa showed the highest survival rate, whereas Bacillus cereus showed the lowest rate, regardless of the type of fabric but the observation of the textiles on the media after extraction showed bacterial growth until the last stage of experiment (28 days), despite the absence of microbial cells in some extracts. Moreover P. aeruginosa turned out to be a best indicator for use in survival experiments, where too intensive growth or no growth was observed, hence not detectable on media. Survival microorganisms in viable state on textile are at least four weeks and can be prolonged in optimal condition.